Legal Implications of Notarial Digitalization on the Validity of Notarial Deeds - Wijaya, Eko; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze: 1) The legal implications of notarial digitization on the validity of notarial deeds. 2) Obstacles and solutions in the notarial digitization process related to the validity of notarial deeds. This type of research falls within the scope of normative legal research. The approach method in this study is a statute approach. The type and source of data in this study are secondary data obtained from literature studies. The analysis in this study is prescriptive. The results of the study conclude: 1) The digitalization of notarial deeds has a significant impact on the validity of notarial deeds, especially because the formal requirements for authentic deeds as stipulated in Indonesian positive law have not yet been met. Although Article 5 paragraph (4) of the ITE Law recognizes electronic documents as legal evidence, the absence of explicit provisions in the Notary Law (UUJN) means that digital notarial deeds cannot yet be equated with conventional authentic deeds. As a result, electronic deeds risk losing their full evidentiary power before the law, creating legal uncertainty, and threatening the protection of the parties' rights. Therefore, regulatory reform containing specific provisions regarding electronic notarial deeds is an urgent need to guarantee validity, evidentiary power, and balanced legal protection in the digital era. 2) In its implementation, the digitalization of notarial deeds faces various obstacles such as legal vacuums, procedural uncertainty, threats to electronic data security, limited understanding of technology among notaries, and the absence of uniform operational standards. These obstacles can hinder the implementation of valid and effective digital deeds. To address this, concrete solutions are needed in the form of comprehensive regulatory updates, the development of digital-based standard operating procedures, strengthening information technology security systems, improving notary digital literacy through ongoing training, and strengthening cross-institutional collaboration. Keywords: Deeds; Digitalization; Notary.